“TO JOKE ABOUT GOD”: ANECDOTES OF HAJI HASAN MUSTAPA - Jajang A Rohmana; Muhamad Zuldin (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2022)
Humor is one of the characteristics of the Sundanese people in West Java. This is not only seen in their conversations about everyday matters but also about serious and sacred issues. They sometimes faced these sacred issues by remaining relaxed and laughing. This, for instance, can be seen in the figure of Haji Hasan Mustapa, a Great Penghulu of Kutaraja and Bandung during the Dutch colonial period. This study focuses on the 209 Sundanese anecdotes of Mustapa that his secretary, M. Wangsaatmaja, collected in Boekoe Singa-Bandoeng (1930) and Boekoe Dongeng djeung Tajarita Sadjarah(1932), as well as those collected by Mustapa's admirer, Ajip Rosidi, in Haji Hasan Mustapa's Jeung Karya-karyana(1989). By using the Adjidarma’s humor theory, which mentions three categories of humor: superiority, incongruity, and extrication, the results show that the incongruous humor category predominates in Mustapa's anecdotes. This can be seen in his incongruous expressions about the nature of God that are out of the ordinary. He did not show his superiority as a respected Dutch official, nor did he extricate himself from various tensions and obstacles. This generally relates to the low level of religious knowledge of his interlocutors. Mustapa’s answers were considered weird and out of the ordinary to them. Therefore, it is understandable that among the Sundanese, Mustapa is known as an eccentric ulama.